Called by God and chosen highlights from the experiences of Christina and Walter Sims in serving Jesus Christ among the children of NSW - Sims, Walter (Lawson, NSW Mission Publications of Australia)
Includes photographs.
Brethren writer.
Keywords: Sims, Christina, -- d. 1975; Child evangelism -- Brethren movement -- Australia -- biography